Engineered patterns of Notch ligands Jag1 and Dll4 elicit differential spatial control of endothelial sprouting - Tiemeijer Laura A.; Ristori Tommaso; Stassen Oscar M.J.A.; Ahlberg Jaakko J.; de Bijl Jonne J.J.; Chen Christopher S.; Bentley Katie; Bouten Carlijn V.C.; Sahlgren Cecilia M. (Elsevier Inc., 2022)
Spatial regulation of angiogenesis is important for the generation of functional
engineered vasculature in regenerative medicine. The Notch ligands Jag1 and
Dll4 show distinct expression patterns in endothelial cells and, respectively, pro-
mote and inhibit endothelial sprouting. Therefore, patterns of Notch ligands may
be utilized to spatially control sprouting, but their potential and the underlying
mechanisms of action are unclear. Here, we coupled in vitro and in silico models
to analyze the ability of micropatterned Jag1 and Dll4 ligands to spatially control
endothelial sprouting. Dll4 patterns, but not Jag1 patterns, elicited spatial con-
trol. Computational simulations of the underlying signaling dynamics suggest
that different timing of Notch activation by Jag1 and Dll4 underlie their distinct
ability to spatially control sprouting. Hence, Dll4 patterns efficiently direct the
sprouts, whereas longer exposure to Jag1 patterns is required to achieve spatial
control. These insights in sprouting regulation offer therapeutic handles for
spatial regulation of angiogenesis.